Strategic Agility as a Driver of SME Performance: The Moderating Role of SME’s Clusters in Indonesia - Nanik Ermawati (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
Strategic agility is a major focus for small and medium-sized enterprises (SMEs) when facing rapidly changing market uncertainties. This study aims to analyze the influence of strategic agility on the performance of SMEs in Indonesia moderated by SME clusters. This study uses a quantitative approach with a survey of SME owners or managers who were sampled with 277 respondents. The data is analyzed using Structural Equation Modeling (SEM-PLS). The study shows that strategic agility has a positive effect on the performance of SMEs, and SME clusters have an effect on strategic agility on the performance of SMEs. This study provides practical implications for SME actors to improve their sensing agility, decision-making agility, and acting agility. Further research is recommended to include moderation or mediation variables such as innovation or environmental uncertainty to enrich the results.